2020
DOI: 10.3390/ijms21218391
|View full text |Cite
|
Sign up to set email alerts
|

Different Sensitivity of Macrophages to Phospholipidosis Induction by Amphiphilic Cationic Drugs

Abstract: Phospholipidosis (PLD), the intracellular accumulation of phospholipids, is an adaptive response to toxic stimuli and serves as an important parameter in the biological assessment of compounds. Cationic amphiphilic drugs are the main inducers of PLD and may impair the function of alveolar macrophages. In vivo and in vitro models are used for PLD screening but the choice of the cellular model may be important because PLD develops in a cell- and species-specific manner. In this study, a panel of different staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In particular, the upregulation of the genes MSMO1 , IDI1 , LSS , and HMGCR suggested enhanced synthesis of cholesterol, and the upregulation of FASN suggested an increased synthesis of fatty acids that may in turn induce phospholipidosis ( Sawada et al, 2005 ; Antherieu et al, 2011 ). This would be in agreement with the reported induction of phospholipidosis by AMI, in various cell types, such as macrophages, alveolar epithelial cells, and hepatocytes ( Lewis et al, 1990 ; Nonoyama and Fukuda, 2008 ; Kapatou et al, 2010 ; Ohlinger et al, 2020 ). However, this upregulation of lipogenic genes was not accompanied by the upregulation of PLIN s that are essential for lipid droplet building and, therefore, lipid storage.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the upregulation of the genes MSMO1 , IDI1 , LSS , and HMGCR suggested enhanced synthesis of cholesterol, and the upregulation of FASN suggested an increased synthesis of fatty acids that may in turn induce phospholipidosis ( Sawada et al, 2005 ; Antherieu et al, 2011 ). This would be in agreement with the reported induction of phospholipidosis by AMI, in various cell types, such as macrophages, alveolar epithelial cells, and hepatocytes ( Lewis et al, 1990 ; Nonoyama and Fukuda, 2008 ; Kapatou et al, 2010 ; Ohlinger et al, 2020 ). However, this upregulation of lipogenic genes was not accompanied by the upregulation of PLIN s that are essential for lipid droplet building and, therefore, lipid storage.…”
Section: Discussionsupporting
confidence: 91%
“…It is also notable that, in this study, human monocyte-derived macrophages (THP-1) and murine macrophages (RAW 264.7) reacted similarly to TcdB in terms of SQSTM1/p62 accumulation and cytokine response but exhibited different sensitivities. A recent study also showed that human and murine macrophages showed different sensitivities to lysosomotropic agents [ 45 ]. Another important aspect that warrants further investigation is whether TcdB-induced lysosome dysfunction during CDI could instigate other downstream pro-inflammatory pathways, including the AIM2 (absent in melanoma 2)/NLRP3 (NLR family pyrin domain containing 3)-inflammasomes, the CGAS (cyclic GMP-AMP synthase)-STING1 (stimulator of interferon response cGAMP interactor 1) pathway and mitochondrial homeostasis, all of which are important for linking lysosome dysfunction to cytokine response [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, J774A.1 cells express a phenotype close to M0 with greater expression of SRAI/II [ 41 ]. Therefore, the effect of nanoarchaeosomes may differ depending on, for instance, the cell genotype because of differences in phospholipid processing [ 45 ] and on the various factors that modulate the expression of SRAI/II. We observed here that nanoARC(ALN) was much less cytotoxic for THP-1 macrophages than for J774A1 cells, probably, because the expression of SRA1 in THP-1 macrophages (and subsequent internalization) is reported to be lower than in J774A1 macrophages [ 43 ].…”
Section: Resultsmentioning
confidence: 99%